The techniques of describing in the journey of " Benefit and Consideration" by Abd EL latif al-Baghdadi - Rouigui, Razika (Journal of Human Sciences, 2020)
This article seeks to acquire and clarify the world of a nomadic text .This can be done by researching the description techniques in "Benefit and Consideration" by the traveler Abd El Latif al-Baghdadi and by emphasizing on the mostimportant description patterns used in the texts of the trip and the most important semantic functions.In our study, we noticed that the subject of description in travel literature did not get so much attention and care compared to other narrative fields such as fiction and story. So there was a strong need to know some concepts from nomadic texts and how to use the description technique , which is the most prominent narrative writing style for travelers .It was based on a set of procedural concepts of contemporary critics such as Philippe Hamon and Gerard Jeanette